Reduced transmission of Klebsiella pneumoniae carbapenemase-producing K. pneumoniae (KPC-KP) in patients with haematological malignancies hospitalized in an Italian hospital during the COVID-19 pandemic. Issue 4 (17th November 2021) - Micozzi, Alessandra; Assanto, Giovanni Manfredi; Cesini, Laura; Minotti, Clara; Cartoni, Claudio; Capria, Saveria; Ciotti, Giulia; Alunni Fegatelli, Danilo; Donzelli, Livia; Martelli, Maurizio; Gentile, Giuseppe
Abstract: Objectives: During the lockdown that started in Italy on 10 March 2020 to address the COVID-19 pandemic, aggressive procedures were implemented to prevent SARS-CoV-2 transmission in SARS-CoV-2-negative patients with haematological malignancies. These efforts progressively reduced Klebsiella pneumonia carbapenemase-producing K. pneumoniae (KPC-KP) spread among these patients. Here we evaluated the potential effects of measures against COVID-19 that reduced KPC-KP transmission. Patients and methods: We analysed KPC-KP spread among 123 patients with haematological malignancies, hospitalized between March and August 2020, who were managed using measures against COVID-19. Their outcomes were compared with those of 80 patients hospitalized during the preceding 4 months (November 2019–February 2020). Results: During March–August 2020, 15.5% of hospitalized patients were KPC-KP positive, compared with 52.5% in November 2019–February 2020 ( P  <   0.0001); 8% and 27.5% of patients in these two groups were newly KPC-KP positive, respectively ( P  =   0.0003). There were eight new KPC-KP-positive patients during January 2020 and none during June 2020. The weekly rate of hospitalized KPC-KP-positive patients decreased from 50% during March 2020 to 17% during August 2020. Four KPC-KP bloodstream infections (BSIs) were experienced by 123 patients (3%) in March–August 2020, and seven BSIs (one fatal) by 80 patients (8%) in November 2019–February 2020 ( P  =   0.02). Consumption and expense of ceftazidime/avibactam administered to KPC-KP-positive patients significantly decreased in March–August 2020. Conclusions: Aggressive strategies to prevent SARS-CoV-2 transmission were applied to all hospitalized patients, characterized by high levels of KPC-KP endemicity and nosocomial transmission. Such measures prevented SARS-CoV-2 infection acquisition and KPC-KP horizontal transmission. Reduced KPC-KP spread, fewer associated clinical complications and decreased ceftazidime/avibactam consumption represented unexpected 'collateral benefits' of strategies to prevent COVID-19.